Artificial leather and light-transmitting device made of the same
By designing specific thickness, weight per unit area and surface color difference in artificial leather, the problem of the lack of light transmission in medium and dark artificial leather is solved, and the effect of light transmission while maintaining texture and touch is achieved, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202180063338.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-29
- Filing Date
- 2021-09-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-09-16
AI Technical Summary
When using suede artificial leather as the skin material for light-transmitting devices in the prior art, medium-dark artificial leather lacks light transmittance, and in order to achieve light transmittance, leather needs to be peeled or welded, resulting in damage to texture, touch and quality.
By designing the thickness, weight per unit area and surface color difference of artificial leather within a specific range, it is able to be light-transmitting without peeling or welding. Specifically, the fiber complex of artificial leather contains extremely fine fibers of 0.1 μm or more than 8 μm, with a thickness of 0.4 mm or more than 1.2 mm, and a weight per unit area of 80 g/m2 or more than 450 g/m2 or less. It also meets specific brightness index and color difference conditions in the CIE1976L*a*b* color space.
It realizes artificial leather with excellent light transmission while maintaining the texture and touch of artificial leather. It is suitable for applications such as home appliances and automotive consoles. Especially when making artificial leather with stuffed, it can maintain the stuffed feel and texture of suede leather, while also having light transmission.
Smart Images

Figure BDA0004126943280000231
Abstract
Description
Technical Field
[0001] The invention relates to artificial leather and a light-transmitting device made of the same. Background Art
[0002] Suede-like artificial leather formed of ultrafine fibers and high molecular weight elastomers has excellent properties that natural leather does not have in terms of durability and uniformity. Taking advantage of these characteristics, suede-like artificial leather is used in a wide range of applications such as clothing, furniture, and automotive interior materials. In recent years, further diversified needs have been generated, and research is also being conducted on various surface materials for home appliances, automotive consoles, etc.
[0003] In such an environment, in recent years, for home appliances and automobile consoles, light-transmitting devices with backlight buttons that emit light themselves (keyboards) have become increasingly popular from the perspective of design. A technology has been proposed to use suede-like artificial leather as a surface material in such light-transmitting devices (for example, see Patent Documents 1 and 2).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2003-71956
[0007] Patent Document 2: Japanese Patent Application Publication No. 2014-185404 Summary of the invention
[0008] Problems to be solved by the invention
[0009] Generally, when artificial leather is used as a surface material, especially for CIE1976L * a * b * The lightness index in the color space (hereinafter sometimes simply referred to as L * For medium and dark artificial leather with a value of 50 or less, it lacks light transmittance, and sometimes is not light-transmissive depending on the color of the artificial leather, the amount of light from the light source, and other conditions. Therefore, in the technologies disclosed in Patent Documents 1 and 2, a cutout portion is provided, or a light-transmissive portion formed by thinning the nonwoven fabric, so as not to provide a portion that substantially blocks light. However, in the case of such technologies, since the artificial leather of the portion that is desired to allow light to pass is removed or welded, there is a problem of damaging the texture, touch, and quality of the artificial leather.
[0010] Therefore, the present invention is completed in view of the above situation, and its purpose is to provide an artificial leather and a light-transmitting device made of the artificial leather, wherein the artificial leather is a dark artificial leather with a medium density or above, and has light transmittance while maintaining its texture and touch.
[0011] Means for solving problems
[0012] The inventors of the present application have repeatedly conducted in-depth research to achieve the above-mentioned purpose, and as a result, found that in an artificial leather of a specific thickness and unit weight, by making the color difference between the design surface and the opposite surface within a specific range, even if no cutout portion is provided and the light-transmitting portion is formed by thinning the non-woven fabric, it is possible to maintain the texture and touch of the artificial leather while having light transmittance. In addition, it was surprisingly found that even when the design surface of the artificial leather is set to a dark color, it still has sufficient light transmittance when used as a light-transmitting device.
[0013] The present invention has been accomplished based on the above findings, and according to the present invention, the following inventions are provided.
[0014] The artificial leather of the present invention is an artificial leather comprising a fiber complex and a polymer elastic body as constituent elements, wherein the fiber complex comprises ultrafine fibers having an average single fiber diameter of 0.1 μm or more and 8 μm or less, the thickness of the artificial leather is 0.4 mm or more and 1.2 mm or less, and the weight per unit area of the artificial leather is 80 g / m 2 Above 450g / m 2 Hereinafter, one surface of the artificial leather is a design surface colored by a dye and / or a pigment, and the artificial leather satisfies the following formulas (1) to (3):
[0015] L * 1≤55···(1)
[0016] L * 0>50···(2)
[0017] ΔL * <-5···(3)
[0018] Here, L * 1 is the CIE1976L of the design surface * a * b * The lightness index in the color space (L * value), L * 0 is the CIE1976L of the surface opposite to the design surface * a * b * The lightness index in the color space (L * value), ΔL* L is the design surface * The L value of the surface opposite to the design surface * The difference between the values (CIELAB1976ab brightness difference, L * 1-L * 0); wherein the brightness index is a value measured under the conditions of CIE standard light source D65 and a viewing angle of 10°.
[0019] According to a preferred embodiment of the artificial leather of the present invention, the above-mentioned fiber-entangled body is dyed with a dye.
[0020] Furthermore, the light-transmitting device of the present invention includes at least one light source and the above-mentioned artificial leather as constituent elements, and the above-mentioned artificial leather is placed on the above-mentioned light source.
[0021] Effects of the Invention
[0022] According to the present invention, an artificial leather having excellent light transmittance while maintaining the texture and touch of artificial leather can be obtained. In particular, the artificial leather of the present invention has excellent light transmittance while being a medium-dark artificial leather that has previously lacked light transmittance, and can therefore be applied to home appliances, automobile consoles, and the like. In particular, when an artificial leather having suede is produced, a highly high-grade artificial leather having light transmittance while maintaining the suede feel and texture can be produced, and can be effectively used for the above-mentioned purposes. DETAILED DESCRIPTION
[0023] The artificial leather of the present invention is an artificial leather comprising a fiber complex and a polymer elastic body as constituent elements, wherein the fiber complex comprises ultrafine fibers having an average single fiber diameter of 0.1 μm or more and 8 μm or less, the thickness of the artificial leather is 0.4 mm or more and 1.2 mm or less, and the weight per unit area of the artificial leather is 80 g / m 2 Above 450g / m 2 Hereinafter, one surface of the artificial leather is a design surface colored by a dye and / or a pigment, and the artificial leather satisfies the following formulas (1) to (3):
[0024] L * 1≤55···(1)
[0025] L * 0>50···(2)
[0026] ΔL * <-5···(3)
[0027] Here, L * 1 is the CIE1976L of the design surface * a * b* The lightness index in the color space (L * value), L * 0 is the CIE1976L of the surface opposite to the design surface * a * b * The lightness index in the color space (L * value), ΔL * L is the design surface * The value and L of the surface opposite to the design surface * The difference between the values (CIELAB1976ab brightness difference, L * 1-L * 0); wherein the brightness index is a value measured under the condition of CIE standard light source D65 and a viewing angle of 10°. The above components are described in detail below, but the present invention is not limited to the scope described below within the scope of the present invention.
[0028] [Ultrafine fiber]
[0029] The average single fiber diameter of the ultrafine fibers constituting the fiber entanglement body, which is one of the components of the artificial leather of the present invention, is 0.1 μm or more and 8 μm or less. By setting the average single fiber diameter to 0.1 μm or more, preferably 0.2 μm or more, and more preferably 0.3 μm or more, an artificial leather having good color fastness, especially good light fastness, can be obtained. On the other hand, by setting the average single fiber diameter to 8.0 μm or less, preferably 4.0 μm or less, and more preferably 2.0 μm or less, a processed leather with good texture can be obtained.
[0030] In addition, the average single fiber diameter of the ultrafine fibers is calculated by the following method.
[0031] In the present invention, the average single fiber diameter of the ultrafine fibers is a value measured and calculated as follows.
[0032] (1) The fiber-entangled body is cut to expose a cross section in the thickness direction which becomes an observation surface.
[0033] (2) A scanning electron microscope (SEM) photograph is taken of a cross section in the thickness direction.
[0034] (3) Randomly select 100 circular or nearly circular elliptical ultrafine fibers.
[0035] (4) The single fiber diameters of the selected ultrafine fibers are measured and their number average value is calculated.
[0036] In addition, the ultrafine fibers of the present invention can use various synthetic fibers formed by polyesters such as polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polyethylene 2,6-naphthalate, polyamides such as 6-nylon, 66-nylon, acrylic acid, polyethylene, polypropylene and other polymers. Among them, from the viewpoint of excellent strength, dimensional stability, light resistance and dyeability, it is preferred to use polyester fibers formed by polymers such as polyethylene terephthalate, polybutylene terephthalate and polytrimethylene terephthalate. In addition, ultrafine fibers of different raw materials can also be mixed in the fiber complex as long as the purpose of the present invention is not impaired.
[0037] Inorganic particles such as titanium oxide particles, lubricants, pigments, heat stabilizers, ultraviolet absorbers, conductive agents, heat storage agents, antibacterial agents, etc. may be added to the ultrafine fibers constituting the fiber entanglement body according to various purposes.
[0038] In addition, as the cross-sectional shape of the ultrafine fibers constituting the fiber-entangled body, in addition to the circular cross-sectional shape, a cross-sectional shape such as an elliptical, flat, polygonal such as a triangle, a fan-shaped, and a cross-shaped cross-sectional shape can be adopted.
[0039] [Fiber complex]
[0040] The fiber-entangled body which is one of the components of the artificial leather of the present invention contains the above-mentioned ultrafine fibers.
[0041] As the form of the fiber complex, woven fabrics, knitted fabrics, nonwoven fabrics, and fiber complexes filled with polymer elastic bodies in these fiber structures can be cited, and they can be used appropriately according to the cost and characteristics required by the application and purpose. From the perspective of cost, woven fabrics and knitted fabrics are preferably used, and from the perspective of a texture with a full feeling and quality brought by fine pile, nonwoven fabrics and fiber complexes filled with polymer elastic bodies are preferably used.
[0042] When a woven knitted fabric is used as the fiber entanglement body, the woven fabrics include plain fabrics, twill fabrics, satin fabrics, and various woven fabrics based on these woven structures. In addition, the knitted fabrics include weft knitting represented by warp knitting and tricot knitting, lace knitting, and various knitted fabrics based on these knitted structures.
[0043] When a nonwoven fabric is used as the fiber entanglement body, all nonwoven fabrics in various categories such as general short-fiber nonwoven fabrics, long-fiber nonwoven fabrics, needle-punched nonwoven fabrics, paper-made nonwoven fabrics, spunbonded nonwoven fabrics, melt-blown nonwoven fabrics, and electrospun nonwoven fabrics can be used. Here, nonwoven fabrics are preferred from the perspective of having a substantial texture and quality due to fine pile.
[0044] Among these fiber-entangled bodies, a fiber-entangled body filled with a polymer elastic body is more preferably used from the viewpoint of excellent durability of the artificial leather and excellent wear resistance of the surface of the artificial leather.
[0045] In addition, in the artificial leather of the present invention, it is a preferred embodiment that the artificial leather contains a woven knitted fabric in its structure from the viewpoint of excellent mechanical strength.
[0046] When the fiber complex includes a woven knitted fabric, the yarn constituting the woven knitted fabric preferably uses synthetic fibers formed of polyester, polyamide, polyethylene, or polypropylene, or copolymers thereof. Among them, synthetic fibers formed of polyester, polyamide, and copolymers thereof can be used alone or in combination or in a mixed manner. In addition, as the yarn constituting the woven knitted fabric, filament yarn, spun yarn (Japanese: spun yarn), and blended yarn of filament and staple fibers can be used.
[0047] Among the woven knitted fabrics included in the fiber complex, it is also possible to use a woven knitted fabric made of composite fibers (hereinafter sometimes described as parallel type composite fibers) composed of two or more polymers in a parallel type or eccentric core-sheath type. For example, in parallel type composite fibers formed by two or more polymers having a difference in intrinsic viscosity (IV), different internal strains are generated between the two components due to the concentration of stress on the high viscosity side during stretching. Due to this internal strain, the high viscosity side shrinks significantly due to the difference in elastic recovery rate after stretching and the difference in thermal shrinkage in the heat treatment process, and strain is generated in the single fiber to present a three-dimensional coil-type curl. Through this three-dimensional coil-type curling, the elasticity of artificial leather is presented.
[0048] As the woven fabric contained in the fiber entanglement body, there can be cited the plain fabric, twill fabric, satin fabric and various woven fabrics based on these woven fabric structures as described above. In addition, as the knitted fabric, any of weft knitting represented by warp knitting and tricot knitting, lace knitting and various knitted fabrics based on these knitted structures can be used. Among them, from the viewpoint of processability, woven fabrics are preferred, and in particular, from the perspective of cost, plain woven fabrics are preferably used. In addition, the weaving density of the woven fabric can be appropriately set according to the total fineness of the yarn strips, the equipment and conditions for entanglement of the nonwoven fabric with the woven knitted fabric described later.
[0049] In addition, in the artificial leather of the present invention, it is also preferred that the fiber complex is dyed with a dye. By reducing the color difference from the design surface as much as possible in advance, it is possible to suppress the emergence (Japanese: ちらつき) caused by the color on the opposite side of the design surface when the artificial leather of the present invention is observed from the design surface, and a sense of unity of the overall color tone can be obtained. The color difference here refers to CIE1976L * a * b *a in color space * Value, b * The difference in value, Δa * Value, Δb * The values are preferably within ±20, more preferably within ±10. It should be noted that the above color difference is the value measured under the CIE standard light source D65 and the viewing angle of 10°. If the color tone of the same system as the design surface is used, a more unified sense of color tone can be obtained. It should be noted that the Δa mentioned here is * Value, Δb * The value is obtained by the method described later.
[0050] [Polymer Elastomer]
[0051] In the artificial leather of the present invention, as described above, by including a polymer elastic body inside the fiber complex, the morphological stability of the artificial leather and the wear resistance of the surface are improved. When the polymer elastic body is included inside the fiber complex, as the polymer elastic body, polyurethane, styrene-butadiene rubber (SBR), nitrile rubber (NBR), and acrylic resin can be used, among which polyurethane is preferably used as the main component. By using polyurethane, an artificial leather having a substantial touch, a leather-like appearance, and a physical property of being resistant to actual use can be obtained.
[0052] When polyurethane is used as the high molecular weight elastic body contained in the fiber complex, any of organic solvent polyurethane used in a state of being dissolved in an organic solvent and water-dispersible polyurethane used in a state of being dispersed in water can be used. In addition, as polyurethane, it is preferred to use a polyurethane obtained by the reaction of a polymer diol, an organic diisocyanate and a chain extender.
[0053] Various additives can be added to the polymer elastomer inside the fiber complex, such as pigments such as carbon black; flame retardants such as phosphorus, halogen and inorganic types; antioxidants such as phenol, sulfur and phosphorus types; ultraviolet absorbers such as benzotriazole, benzophenone, salicylate, cyanoacrylate and oxalic acid aniline types; light stabilizers such as hindered amine and benzoate types; hydrolysis stabilizers such as polycarbodiimide; plasticizers; antistatic agents; surfactants; coagulant regulators and dyes, etc.
[0054] The content of the polymer elastic body inside the fiber entanglement can be appropriately adjusted in consideration of the type of polymer elastic body used, the manufacturing method of the polymer elastic body, the texture and physical properties. The content of the polymer elastic body is preferably 5% by mass or more and 80% by mass or less, more preferably 10% by mass or more and 60% by mass or less, and further preferably 15% by mass or more and 45% by mass or less, relative to the mass of the fiber entanglement. By making the content ratio of the polymer elastic body 5% by mass or more, the sheet strength can be obtained, and the entanglement state can be maintained by bonding the fibers. On the other hand, by making the content ratio 80% by mass or less, the texture can be prevented from becoming hard.
[0055] [Artificial leather]
[0056] The artificial leather of the present invention comprises the above-mentioned fiber-entangled body and a polymer elastic body as components.
[0057] In addition, the thickness of the artificial leather of the present invention is 0.4mm or more and 1.2mm or less. By making the thickness of the artificial leather be 0.4mm or more, preferably 0.5mm or more, more preferably 0.6mm or more, it is possible to obtain the strength and elongation required for the artificial leather. On the other hand, by making it be 1.2mm or less, preferably 1.0mm or less, more preferably 0.8mm or less, it is possible to easily obtain the light-transmitting artificial leather as the object of the present invention.
[0058] The thickness of artificial leather refers to a value measured and calculated according to the following procedure in accordance with "8.4 Thickness Method A" of JIS L1096:2010 "Test methods for grey fabrics of woven and knitted fabrics".
[0059] (1) The sample to be measured is pre-dried in an environment with a relative humidity of 10 to 25% and a temperature below 50°C, and then placed in a standard room to prepare the sample under a constant weight.
[0060] (2) The thickness (mm) of the prepared sample was measured at five different locations using a thickness gauge for 10 seconds at a pressure of 0.7 kPa, and the average value was calculated and rounded to the second decimal place.
[0061] Furthermore, the weight per unit area of the artificial leather of the present invention is 80 g / m 2 Above 450g / m 2 By making the weight per unit area of artificial leather 80g / m 2 More than, preferably 100g / m 2 More preferably 120g / m 2 On the other hand, by making it 450g / m 2Below, preferably 400g / m 2 Below, more preferably 350g / m 2 Next, it will be described how it is easier to obtain the light-transmitting artificial leather that is the object of the present invention.
[0062] The basis weight of artificial leather is a value calculated by measuring according to the following procedure in accordance with "8.3.2 Mass per unit area under standard conditions (Method A)" of JIS L1096:2010 "Test methods for grey fabrics of woven and knitted fabrics".
[0063] (1) For the test sample, pre-dry it in an environment with a relative humidity of 10-25% and a temperature below 50°C, and place it in a standard room. When the constant weight is reached, collect two test pieces of about 200 mm × 200 mm, measure the mass (g) of each standard state, and calculate the mass per 1m by the following formula: 2 Mass (g / m 2 ), calculate the average value and round it to the first decimal place.
[0064] Sm=W / A
[0065] Here,
[0066] Sm: mass per unit area under standard conditions (g / m 2 )
[0067] W: The mass of the test piece under standard conditions (g)
[0068] A: Area of the test piece (m 2 )
[0069] Furthermore, one surface of the artificial leather of the present invention is a design surface colored with a dye and / or a pigment, and the artificial leather satisfies the following formulas (1) to (3).
[0070] L * 1≤55···(1)
[0071] L * 0>50···(2)
[0072] ΔL * <-5···(3)
[0073] Here, L * 1 is the CIE1976L of the design surface * a * b * The lightness index in the color space (L * value), L * 0 is the CIE1976L of the surface opposite to the design surface* a * b * The lightness index in the color space (L * value), ΔL * L is the design surface * The value and L of the surface opposite to the design surface * The difference between the values (CIELAB1976ab brightness difference, L * 1-L * 0). It should be noted that the brightness index is a value measured under the condition of CIE standard light source D65 and a viewing angle of 10°.
[0074] That is, as shown in the above formula (1), L * 1≤55 means that the design surface is medium dark to dark. According to the present invention, even if L * Artificial leather with a deep color of 1≤30 and excellent light transmittance.
[0075] In addition, as shown in the above formula (2), L * 0>50 means that the color is lighter than the design surface when measured from the surface opposite to the design surface, and the ΔL shown in the above formula (3) is satisfied. * <-5, that is, by ΔL * The color difference caused is above a certain level, and the light transmittance can be improved even for dark design surfaces.
[0076] Preferably L * 0>60, more preferably L * 0>70. As the upper limit, from the viewpoint of design, that is, in order to be less susceptible to the color tone on the opposite side of the design surface, L is preferred. * 0≤90.
[0077] In addition, ΔL * <-5, preferably ΔL * <-10, more preferably ΔL * <-15.
[0078] [Manufacturing method of artificial leather]
[0079] Here, the method for producing the artificial leather of the present invention is described. The artificial leather of the present invention can be obtained, for example, by using ultrafine fiber-developing fibers formed of two or more polymer substances having different solubility in a solvent.
[0080] As the ultrafine fiber-developing fiber, there can be used: a sea-island type composite fiber in which two thermoplastic resin components with different solubility in a solvent are used as a sea component and an island component, and the sea component is dissolved and removed by using a solvent to make the island component into ultrafine fibers; a strippable composite fiber in which two thermoplastic resin components are alternately arranged radially or in multiple layers on the fiber surface, and the fibers are stripped and split by solvent treatment to form ultrafine fibers; etc. Among them, the sea-island type composite fiber can provide appropriate gaps between the island components, that is, between the ultrafine fibers inside the fiber bundle, by removing the sea component, and is therefore preferably used from the viewpoint of the softness and texture of the base material.
[0081] In the manufacture of sea-island type composite fibers, a polymer array method in which the two components, the sea component and the island component, are arranged relative to each other using a sea-island type composite spinneret and the spinning is performed, and a mixed spinning method in which the two components, the sea component and the island component, are mixed and the spinning is performed, etc. From the perspective of obtaining extremely fine fibers with uniform fineness, it is more preferred to use a method for manufacturing sea-island type composite fibers based on a polymer array method.
[0082] The preferred method is to form a nonwoven fabric (ultrafine fiber web) in the fiber complex. By forming a nonwoven fabric, a uniform and beautiful appearance and texture can be obtained. The nonwoven fabric (ultrafine fiber web) can be in the form of either a short fiber nonwoven fabric or a long fiber nonwoven fabric.
[0083] The fiber length of the ultrafine fibers when making a short fiber nonwoven fabric can be appropriately selected according to the form of the nonwoven fabric. The fiber length in the case of a conventional short fiber nonwoven fabric is preferably 25 mm or more and 90 mm or less. By making the fiber length of the ultrafine fibers less than 90 mm, good quality and texture can be obtained, and by making the fiber length more than 25 mm, artificial leather with good wear resistance can be obtained. In addition, the fiber length in the case of a nonwoven fabric obtained by a papermaking method is preferably 0.1 mm or more and 10 mm or less. By making the fiber length less than 10 mm, a stable suspension can be obtained, and the unevenness of the unit area weight and thickness of the nonwoven fabric can be suppressed. In addition, by making the fiber length more than 0.1 mm, the fluff from the nonwoven fabric can be suppressed from falling off. In addition, for the ultrafine fiber generating fiber of the present invention, in order to promote the entanglement of the fibers with each other, it is preferably subjected to a curling process. Curling and cutting processes can use known methods.
[0084] Next, the obtained raw cotton is made into a fiber web by a cross-lapper or the like, and then entangled to obtain a nonwoven fabric. As a method for entanglement of the fiber web to obtain a nonwoven fabric, a needle punch method, a water jet punch, etc. can be used. In addition, the weight per unit area of the fiber web can be appropriately set in consideration of the design of the final product, the dimensional change in the subsequent process, the characteristics of the processing machine, etc.
[0085] In addition, it is also a preferred method to integrate the woven knitted fabric with the fiber entanglement body formed by the ultrafine fiber generating fiber to obtain a laminated sheet of a nonwoven fabric formed by the ultrafine fiber generating fiber and the woven knitted fabric. As a method for integrating the two, methods such as needle punching and water entanglement can be used. Among them, from the perspective of fit and product quality, it is preferred to use needle punching for entanglement. For the laminated sheet of the fiber entanglement body formed by the ultrafine fiber generating fiber and the woven knitted fabric thus obtained, from the perspective of densification, it is a preferred method to shrink it by dry heat or wet heat or both before imparting the polymer elastomer and then make it high-densified. The shrinkage treatment can be performed before the ultrafine fibers are revealed, or it can be performed after the ultrafine fibers are revealed, but in terms of being able to utilize the characteristics of the sea component polymer of the ultrafine fiber generating fiber, it is a preferred method to perform the shrinkage treatment before the ultrafine fibers are generated. In addition, the area shrinkage rate of the laminated sheet in the shrinkage process is preferably in the range of 15% to 35%. By making the area shrinkage rate 15% or more, the quality improvement effect caused by shrinkage can be ideally obtained. In addition, by making the area shrinkage rate 35% or less, it is possible to leave room for shrinkage on the woven knitted fabric integrated with the nonwoven fabric, so that it can be efficiently shrunk after the polymer elastomer is applied later. The more preferred range of the area shrinkage rate is 1% to 30%, and more preferably 15% to 25%. For the method of measuring the area shrinkage rate, the shrinkage rate in the length direction and the shrinkage rate in the width direction are calculated from the length and width before and after processing in the shrinkage process, and calculated using the following calculation formula.
[0086] Length shrinkage ratio = length after shrinkage / length before shrinkage
[0087] Width shrinkage ratio = width after shrinkage / width before shrinkage
[0088] Area shrinkage rate (%) = (1-(1-length shrinkage rate)×(1-width shrinkage rate))×100.
[0089] As the shrinking method, known methods such as hot water shrinkage, steam shrinkage, dry heat shrinkage, etc. can be used. The time and temperature of the shrinkage treatment can be adjusted according to the shrinking method adopted, the type of fibers constituting the fiber entanglement, etc., so as to achieve the above-mentioned area shrinkage rate.
[0090] The method for producing artificial leather of the present invention comprises: treating a laminated sheet of a fiber entanglement body formed by the above-mentioned ultrafine fiber generating fiber and a woven knitted fabric to produce ultrafine fibers having an average single fiber diameter of 0.1 μm or more and 8 μm or less. As a method for producing ultrafine fibers, a method of dissolving one side of the resin constituting the ultrafine fiber generating fiber using a solvent can be cited. In particular, for an ultrafine fiber generating sea island composite fiber in which the sea component is formed by an easily soluble polymer and the island component is formed by a poorly soluble polymer, a method of dissolving the sea component is preferred.
[0091] As a solvent for dissolving the sea component, when the sea component is a polyolefin such as polyethylene or polystyrene, an organic solvent such as toluene or trichloroethylene is used. In addition, when the sea component is polylactic acid or copolyester, an alkaline aqueous solution such as sodium hydroxide can be used. In addition, the ultrafine fiber production process (sea removal treatment) can be performed by immersing the fiber entanglement formed by the ultrafine fiber production type fiber in a solvent and squeezing the liquid.
[0092] Next, the obtained fiber complex containing ultrafine fibers is subjected to a treatment of imparting a polymer elastomer. The method of either the treatment of making the ultrafine fibers appear from the ultrafine fiber-revealing fibers or the treatment of imparting a polymer elastomer can be carried out first. In the case where the ultrafine fiber manifestation treatment is carried out first, since the polymer elastomer holds the ultrafine fibers, the ultrafine fibers will not fall off, and the fiber complex can withstand longer-term use. In addition, in the case where the polymer elastomer is imparted first, since the structure of the polymer elastomer not holding the ultrafine fibers is formed, artificial leather with good texture can be obtained. Which one to carry out first can be appropriately selected according to the type of polyurethane used, etc.
[0093] In addition, when the polymer elastomer is applied after the ultrafine fiber development treatment, it is preferred to provide a step of applying a water-soluble resin between the two steps. By providing the step of applying the water-soluble resin, the surface of the fiber bundles and woven knitted fabrics constituting the ultrafine fibers is protected by the water-soluble resin, and the parts directly bonded to the polymer elastomer on the surface of the fiber bundles and woven knitted fabrics constituting the ultrafine fibers are not continuous but intermittent, and the bonding area can be appropriately suppressed. As a result, a good hand feeling brought by the polymer elastomer and a soft texture can be obtained, and when a woven knitted fabric formed by parallel type composite fibers is used, an artificial leather with high elasticity can be obtained.
[0094] As such a water-soluble resin, polyvinyl alcohol, polyethylene glycol, sugars, starch, etc. can be used. Among them, polyvinyl alcohol having a saponification degree of 80% or more is preferably used.
[0095] As a method of imparting a water-soluble resin to a fiber complex, there can be cited a method of impregnating the fiber complex with an aqueous solution of the water-soluble resin and drying the fiber complex, etc. From the viewpoint of suppressing the shrinkage of the woven knitted fabric, the drying conditions such as the drying temperature and the drying time are preferably such that the temperature of the fiber complex itself to which the water-soluble resin is imparted is suppressed to below 110°C.
[0096] The amount of water-soluble resin applied is preferably 1 to 30% by mass relative to the mass of the fiber complex immediately before application. By making the amount applied 1% by mass or more, a good texture can be obtained, and in the case of using artificial leather made of woven knitted fabrics formed by parallel type composite fibers, good elasticity can be obtained. In addition, by making the amount applied 30% by mass or less, an artificial leather with good processability and good physical properties such as wear resistance can be obtained. In addition, in the subsequent steps, the amount of polymer elastomer that can be applied to the fiber complex increases, so that the high density of the artificial leather and the densification of the touch become possible.
[0097] In the method for manufacturing artificial leather of the present invention, the fiber complex (precursor sheet of artificial leather) endowed with a polymer elastic body can be subjected to a process of cutting the fiber complex (precursor sheet of artificial leather) in half in the plane direction. By including the half-cutting process, the productivity of artificial leather can be improved. For example, as a method for laminating woven knitted fabrics, in the case of adopting a method of sandwiching a non-woven fabric layer formed of ultrafine fiber-generating fibers with a woven knitted fabric layer, it is a preferred method to cut the precursor sheet in half and set the inner surface as a pile surface as a method for achieving dense quality.
[0098] The artificial leather of the present invention preferably has pile on at least one side. The pile treatment can be performed by polishing the surface of the precursor sheet of the artificial leather using sandpaper, a roller grinder, etc. In particular, by using sandpaper, a uniform and dense pile can be formed. Furthermore, in order to form a uniform pile on the surface of the precursor sheet of the artificial leather, it is preferred to reduce the grinding load.
[0099] The obtained artificial leather precursor sheet can be dyed. * a * b * The lightness index in the color space (L * The artificial leather can be dyed in a manner that the value) is within the scope of the present invention. As a dyeing method, the precursor sheet of the artificial leather is prepared in advance, and there is no particular problem in the method of dyeing with a general dye suitable for the fiber material. When dyeing, a dye that matches the fiber base material of the artificial leather can be used. If the fiber base material is a polyester fiber, a disperse dye can be used. If it is a polyamide fiber, an acid dye, a gold-containing dye, etc., which are usually used when dyeing polyamide, can be used.
[0100] Dyeing is performed using disperse dyes, cationic dyes or other reactive dyes, and is preferably performed using a high-temperature and high-pressure dyeing machine in order to make the texture of the dyed artificial leather substrate soft.
[0101] The artificial leather of the present invention has a design surface colored by dye and / or pigment. The coloring of the design surface is based on the above L * Value and design surface L * The value and L of the surface opposite to the design surface * The difference between the values ΔL * Coloring is performed so as to satisfy the range specified in the present invention. In order to obtain the colored layer colored with a dye and / or a pigment on the design surface, a printing technique such as dye printing or pigment printing can be used.
[0102] For dye printing, dyes that match the fiber base material of the artificial leather can be used. If the fiber base material is polyester fiber, disperse dyes can be used. If it is polyamide fiber, acid dyes, gold-containing dyes, and other dyes commonly used when dyeing polyamide can be used. As a printing method, any method such as transfer printing, screen printing, and inkjet printing can be used without limitation.
[0103] Regarding pigment printing, a material obtained by mixing a binder resin in a pigment can be used, and as the binder resin, urethane resin, acrylic resin, silicone resin, etc. can be used without particular limitation. As a printing method, as with dye printing, any method such as transfer printing, screen printing, inkjet printing, etc. can be used without limitation.
[0104] As another method, there is no particular problem in a method in which artificial leather (artificial leather base material) is prepared in advance before forming the colored layer and then colored with a dye, pigment, or the like.
[0105] Furthermore, as required, finishing treatment with softeners such as silicone, antistatic agents, hydrophobic agents, flame retardants, and lightfast agents can be performed. The finishing treatment can be performed after dyeing or in the same bath as dyeing. Flame retardant treatment can use known halogen flame retardants such as bromine and chlorine or non-halogen flame retardants such as phosphorus, and can be applied by dipping after dyeing or by back coating such as blade coating or rotary screen method.
[0106] There is no limitation on whether these finishing treatments are performed before or after the coloring layer is formed, but in order to form a uniform coloring layer, the finishing treatments are preferably performed after the coloring layer is formed. In addition, these finishing treatment agents can also be processed simultaneously when the coloring layer is formed, but as mentioned above, in order to form a uniform coloring layer, the finishing treatments are preferably performed after the coloring layer is formed.
[0107] [Light-transmitting device]
[0108] The artificial leather of the present invention is light-transmissive and thus is suitable for use in a light-transmissive device. The light-transmissive device comprises at least one light source and the artificial leather as components, and the artificial leather is placed on the light source. Since the artificial leather of the present invention is light-transmissive, the light of the light source can be transmitted through the artificial leather of the present invention for visual recognition.
[0109] There is no particular limitation on the light source constituting the light-transmitting device of the present invention, but since it needs to be built into the device, it is preferred to use a field-induced luminescent light emitting diode (LED) or electroluminescent (EL) as a small light source. The wavelength that can be used is also not particularly limited, as long as it is visible light of 380nm to 780nm. In addition, the illumination of the light source is not particularly limited, but from the perspective of light transmittance, it is preferably 20001x or more.
[0110] When used in the above-mentioned light-transmitting device, at least the portion of the artificial leather that requires light transmission satisfies the above-mentioned formulas (1) to (3), but the color tone of other portions that do not require light transmission can be constructed with the same design surface or with a free design.
[0111] Example
[0112] Next, the artificial leather of the present invention is further specifically described using examples, but the present invention is not limited to these examples. Next, the evaluation method and measurement conditions used in the examples are described. However, in the measurement of each physical property, the measurement is based on the above method unless otherwise specified.
[0113] [Measurement method]
[0114] (1) Average single fiber diameter of ultrafine fibers
[0115] The ultrafine fibers were observed using a scanning electron microscope (SEM) of "VE-7800" manufactured by Keyence Corporation, and the average single fiber diameter was calculated.
[0116] (2) Thickness
[0117] As mentioned above, the calculation is performed using the JIS L1096:2010 8.4A method.
[0118] (3) Weight per unit area
[0119] As mentioned above, the calculation is performed using JIS L1096:2010 8.3.2A method.
[0120] (4) CIE1976L * a * b * Lightness index in color space
[0121] Measured using a spectrophotometer JIS Z 8781-4:2013 "Color Measurement - Part 4: CIE1976L * a * b * L specified in 3.3 of "Color Space" * 、a * 、b * The value is obtained by measuring the design surface and the surface opposite to the design surface (the back of the design surface) five times under the conditions of CIE standard light source D65 and a viewing angle of 10°. ΔL is calculated by the following formulas: * , Δa * , Δb * Note that the measurement was performed using "CR-310" manufactured by Konica Minolta, Inc.
[0122] ΔL * =L * 1-L * 0
[0123] Δa * =a * 1-a * 0
[0124] Δb * =b * 1-b * 0
[0125] Here,
[0126] L * 1: CIE1976L for design surface * a * b * The lightness index in the color space (L * value)
[0127] L * 0: CIE1976L of the surface opposite to the design surface * a * b * The lightness index in the color space (L * value),
[0128] ΔL * L is the design surface * The value and L of the surface opposite to the design surface * The difference between the values (CIELAB1976ab brightness difference, L * 1-L * 0)
[0129] a *1: CIE1976L for design surface * a * b * The lightness index in the color space (a * value)
[0130] a * 0: CIE1976L of the surface opposite to the design surface * a * b * The lightness index in the color space (a * value),
[0131] Δa * a for the design surface * The value and a of the surface opposite to the design surface * The difference between the values (CIELAB1976a * Poor, a * 1-a * 0)
[0132] b * 1: CIE1976L for design surface * a * b * The brightness index in the color space (b * value)
[0133] b * 0: CIE1976L of the surface opposite to the design surface * a * b * The brightness index in the color space (b * value),
[0134] Δb * b is the design surface * The value and b of the surface opposite to the design surface * The difference between the values (CIELAB1976b * Poor, b * 1-b * 0).
[0135] (5) Light transmittance
[0136] In order to confirm the light transmittance, as the spectral transmittance measurement, a spectrophotometer "V-770" (ISN-923 integrating sphere) manufactured by JASCO Corporation was used, and a "Spectralon Reflectance Standard" manufactured by Labsphere was used as a standard white plate. The spectral transmittance (%) was measured in the region of 400 to 800 nm with a bandwidth of 5 nm.
[0137] The measurement is carried out by incident light from the opposite side of the design surface (the back side of the design surface). 0.2% or more is considered to have light transmittance, which is recorded as ○ (B) in Table 1, and 3.0% or more is considered to have better light transmittance, which is recorded as ◎ (A) in Table 1. In the case of less than 0.2%, it is considered to have no light transmittance, which is recorded as × (C).
[0138] (6) Texture
[0139] As the texture evaluation, the case where the texture had a smooth feeling peculiar to artificial leather was marked as ○ (A), and the case where the texture had a rough feeling was marked as × (B), and the results are shown in Table 1.
[0140] (7) The color on the side opposite to the design emerges
[0141] Observe from the design surface and visually determine whether the color on the opposite side of the design surface emerges. The case where no emergence occurs is recorded as ○ (A), the case where some emergence occurs but is practical is recorded as Δ (B), and the case where emergence occurs is recorded as × (C), and the results are recorded in Table 1.
[0142] (8) Comprehensive judgment
[0143] The evaluation results of light transmittance, texture, and color emergence on the opposite side of the design surface were used as a comprehensive judgment, with the case where it is suitable for use in a light-transmitting device being evaluated as ◎ (A), the case where it can be used being evaluated as ○ (B), and the case where it cannot be used as a light-transmitting device being evaluated as × (C).
[0144] [Example 1]
[0145] <Raw Cotton>
[0146] Polyethylene terephthalate is used as the island component and polystyrene is used as the sea component. A sea-island type composite spinneret with 16 islands is used. Melt spinning is performed at an island / sea mass ratio of 80 / 20, and then the fibers are stretched and curled. Thereafter, the fibers are cut into 51 mm in length to obtain raw cotton of the sea-island type composite fibers.
[0147] <Laminated sheets of nonwoven fabric and woven fabric>
[0148] The raw cotton of the island-in-sea composite fiber is carded and cross-lapped to form a laminated web (nonwoven fabric). In order to suppress wrinkles in the woven fabric caused by the rapid width change after lamination, 100 strands / cm 2Needle punching was performed with the number of perforations. In addition, a monofilament formed of a single component with an intrinsic viscosity (IV) of 0.65 and a multifilament (84 dtex, 72 filaments) with a twist of 2500 T / m was used as a weft yarn, and a monofilament formed of a single component with an intrinsic viscosity (IV) of 0.65 and a multifilament (84 dtex, 72 filaments) with a twist of 2500 T / m was used as a warp yarn to weave a plain fabric with a weaving density of 97 warps / 2.54 cm and 76 wefts / 2.54 cm. The obtained plain fabric was stacked on the upper and lower sides of the above-mentioned stacked web (nonwoven fabric).
[0149] Then, at 2500 strands / cm 2 The number of perforations (density) was needle punched to obtain a unit area weight of 740g / m 2 , a laminated sheet consisting of a nonwoven fabric of ultrafine fiber-generating fibers having a thickness of 3.4 mm and a heat-shrinkable woven fabric.
[0150] <Fiber Entanglement>
[0151] The laminated sheet obtained by the above process is treated with hot water at a temperature of 96°C to shrink it, then impregnated with a polyvinyl alcohol (hereinafter sometimes referred to as PVA) aqueous solution, and dried with hot air at a temperature of 110°C for 10 minutes, thereby obtaining a sheet substrate having a PVA mass of 7.6% by mass relative to the mass of the laminated sheet. The sheet substrate thus obtained is immersed in trichloroethylene to dissolve and remove the polystyrene of the sea component, thereby obtaining a sea-free sheet formed by entanglement of ultrafine fibers with an average single fiber fineness of 4.4 μm and plain fabric. The sea-free sheet formed by the non-woven fabric containing ultrafine fibers and plain fabric obtained in this way is immersed in a dimethylformamide (hereinafter sometimes referred to as DMF) solution of polyurethane adjusted to a solid content concentration of 12%, and then the polyurethane is coagulated in an aqueous solution with a DMF concentration of 30%. Thereafter, PVA and DMF were removed with hot water, and the mixture was dried with hot air at 110° C. for 10 minutes, thereby obtaining a precursor sheet of a fiber-entangled body having a polyurethane mass of 27% by mass relative to the total mass of the ultrafine fibers formed of the island components and the above-mentioned plain woven fabric.
[0152] The precursor sheet of the fiber complex thus obtained is cut in half in the thickness direction perpendicularly to the thickness direction, and the non-woven fabric layer inside the precursor sheet is ground with circular sandpaper with a sandpaper count of 320 to form a velvet surface on the surface layer, thereby obtaining a fiber complex with a thickness of 0.90 mm.
[0153] <Coloring method of the design surface and the side opposite to the design surface (back side of the design surface)>
[0154] The fiber complex thus obtained was dyed into L using a liquid jet dyeing machine with disperse dyes. *The light gray color with a value of 50 or more is then subjected to reduction cleaning, dried in a dryer, and then pigment printed on the design surface in a screen printer. Black pigment and urethane resin are used as a binder in pigment printing. Thus, the L value of the design surface is obtained. * The value is 20.08, the L on the back of the design surface * The fiber entangled body has a L value of 70.86. The L value of the surface opposite to the design surface is * The difference between the values ΔL * The spectral transmittance was -50.78, and the result of measuring the spectral transmittance was 1.5%, confirming that it has light transmittance. * Value, Δb * The values were all within ±20, and the color was the same color, so there was no color on the opposite side of the design surface. The texture was also good, confirming that it was suitable for use in light-transmitting devices. The results are shown in Table 1.
[0155] [Example 2]
[0156] <Raw cotton~Fiber complex>
[0157] The same ones as in Example 1 were used.
[0158] <How to color the design surface and the side opposite to the design surface (back side of the design surface)>
[0159] In addition to making the design surface and back surface L as shown in Table 1 * The obtained fiber complex was dyed in the same manner as in Example 1 except for the gray value. Then, it was reduced and washed, dried in a dryer, and then pigmented on the design surface in a screen printer. In pigment printing, gray pigment and urethane resin were used as binders. Thus, the L value of the design surface was obtained. * The value is 50.34, and the L on the back of the design surface * The fiber entangled body has a L value of 56.53. The L value of the surface opposite to the design surface is * The difference between the values ΔL * The result of measuring the spectral transmittance was 2.2%, confirming that it has light transmittance. * Value, Δb * The values are all within ±20, and the color is the same color, so there is no color on the opposite side of the design surface. The texture is also good, confirming that it is suitable for light-transmitting devices.
[0160] The results are shown in Table 1.
[0161] [Example 3]
[0162] <Raw cotton~fiber complex>
[0163] The same ones as in Example 1 were used.
[0164] <Coloring method of the design surface and the side opposite to the design surface (back side of the design surface)>
[0165] In addition to making the design surface back side L listed in Table 1 * The obtained fiber entangled body was dyed in the same manner as in Example 1 except for the light gray value. Then, reduction washing was performed, and after drying in a dryer, dye printing was performed on the design surface using a dark gray disperse dye in a screen printer. Thus, the L value of the design surface was obtained. * The value is 33.98, and the L on the back of the design surface * The fiber entangled body has a L value of 72.20. The L value of the surface opposite to the design surface is * The difference between the values ΔL * The spectral transmittance was -38.22, and the result of measuring the spectral transmittance was 2.7%, confirming that it has light transmittance. * Value, Δb * The values are all within ±20, and the color is the same color, so there is no color on the opposite side of the design surface. The texture is also good, confirming that it is suitable for light-transmitting devices.
[0166] The results are shown in Table 1.
[0167] [Example 4]
[0168] <Raw cotton~fiber complex>
[0169] The same ones as in Example 1 were used.
[0170] <Coloring method of the design surface and the side opposite to the design surface (back side of the design surface)>
[0171] In addition to making the design surface back side L listed in Table 1 * The obtained fiber entangled body was dyed in the same manner as in Example 1 except for the light gray value. Then, reduction washing was performed, and after drying in a dryer, a gray disperse dye was dye-printed on the design surface in a screen printer. Thus, the L value of the design surface was obtained. * The value is 52.44, and the L on the back of the design surface * The fiber entangled body has a L value of 72.20. The L value of the surface opposite to the design surface is * The difference between the values ΔL * The spectral transmittance was -19.76, and the result of measuring the spectral transmittance was 2.9%, confirming that it has light transmittance. * Value, Δb * The values are all within ±20, and the color is the same color, so there is no color on the opposite side of the design surface. The texture is also good, confirming that it is suitable for light-transmitting devices.
[0172] The results are shown in Table 1.
[0173] [Example 5]
[0174] <Raw cotton~fiber complex>
[0175] The same ones as in Example 1 were used.
[0176] <Coloring method of the design surface and the side opposite to the design surface (back side of the design surface)>
[0177] The obtained fiber entangled body is printed with only blue pigment on the design surface. * The value is 36.88, and the L on the back of the design surface * The fiber entangled body has a L value of 88.14. The L value of the surface opposite to the design surface is 88.14. * The difference between the values ΔL * The result of measuring the spectral transmittance was 5.1%, confirming that it has light transmittance. * The value is within ±20, but Δb * The value is 39.97, which is more than ±20, so the white color on the opposite side of the design surface can be seen from the design surface, and the color emerges. The texture is good and it is confirmed that it can be used for light-transmitting devices. The results are shown in Table 1.
[0178] [Example 6]
[0179] <Raw cotton~Fiber entanglement>
[0180] The same ones as in Example 1 were used.
[0181] <Coloring method of the design surface and the side opposite to the design surface (back side of the design surface)>
[0182] The obtained fiber entangled body was subjected to gray pigment printing only on the design surface as in Example 2. Thus, the L * The value is 50.34, and the L on the back of the design surface * The fiber entangled body has a L value of 88.14. The L value of the surface opposite to the design surface is 88.14. * The difference between the values ΔL * The spectral transmittance was -37.80, and the result of measuring the spectral transmittance was 5.8%, confirming that it has light transmittance. * Value, Δb * The values were all within ±20 for the same color, and there was no color on the opposite side of the design surface. The texture was also good, confirming that it was suitable for use in light-transmitting devices. The results are shown in Table 1.
[0183] [Comparative Example 1]
[0184] <Raw cotton~fiber complex>
[0185] The same ones as in Example 1 were used.
[0186] <Coloring method of the design surface and the side opposite to the design surface (back side of the design surface)>
[0187] The obtained fiber complex is dyed into L using a liquid flow dyeing machine with disperse dyes. * The L value is less than 50, and then the design surface and the back side of the design surface are obtained. * The fiber entanglement body has a L value of 27.33. * The difference between the values ΔL * is 0.00, and the result of measuring the spectral transmittance is 0.0%, indicating no light transmittance. * Value, Δb * The values were all within ±20, and there was no color on the opposite side of the design surface, but since there was no light transmittance, it was confirmed that it could not be used for light-transmitting devices. The results are shown in Table 1.
[0188] [Comparative Example 2]
[0189] <Raw cotton~Fiber complex>
[0190] The same ones as in Example 1 were used.
[0191] <Coloring method of the design surface and the side opposite to the design surface (back side of the design surface)>
[0192] The fiber complex thus obtained was dyed into L using a liquid jet dyeing machine using disperse dyes. * The gray color with a value of less than 50 is then reduced and cleaned, dried in a dryer, and then printed with black pigment on the design surface in a screen printer. * The value is 22.50, the L on the back of the design surface * The fiber entangled body has a L value of 44.02. The L value of the surface opposite to the design surface is * The difference between the values ΔL * is -21.52, and the result of measuring the spectral transmittance is 0.0%, indicating no light transmittance. * Value, Δb * The values were all within ±20, and there was no color on the opposite side of the design surface, but since there was no light transmittance, it was confirmed that it could not be used for light-transmitting devices. The results are shown in Table 1.
[0193] [Comparative Example 3]
[0194] <Raw cotton~fiber complex>
[0195] The same ones as in Example 1 were used.
[0196] <Coloring method of the design surface and the side opposite to the design surface (back side of the design surface)>
[0197] The fiber complex thus obtained was dyed dark gray using a liquid jet dyeing machine using the same dyeing recipe as in Comparative Example 1, then subjected to reduction cleaning, dried using a dryer, and then printed with gray pigment on the design surface using a screen printer. * The value is 50.34, the L on the back of the design surface * The fiber entanglement body has a L value of 27.33. The L value of the surface opposite to the design surface is * The difference between the values ΔL * is 23.01, and the result of measuring the spectral transmittance is 0.0%, indicating no light transmittance. * Value, Δb * The values were all within ±20, and there was no color on the opposite side of the design surface, but since there was no light transmittance, it was confirmed that it could not be used for light-transmitting devices. The results are shown in Table 1.
[0198] [Table 1]
[0199]
Table 1
[0200]
[0201] As shown in Table 1, the results of the artificial leathers of Examples 1 to 6 were spectral transmittances of 0.2% or more and had light transmittance. On the other hand, the artificial leathers of Comparative Examples 1 to 3 all had spectral transmittances of 0.0% and had no light transmittance. In particular, it is worth mentioning that Example 1 has good light transmittance despite having a dark black design surface equal to or higher than that of Comparative Example 1.
Claims
1. A light-transmitting device comprising at least artificial leather and at least one light source as constituent elements, wherein the artificial leather is placed on the light source. The artificial leather comprises a fiber complex and a polymer elastic body as constituent elements, the fiber complex comprises ultrafine fibers having an average single fiber diameter of 0.1 μm to 8 μm, the thickness of the artificial leather is 0.4 mm to 1.2 mm, and the weight per unit area of the artificial leather is 80 g / m 2 Above 450g / m 2 Hereinafter, one surface of the artificial leather is a design surface colored by a dye and / or a pigment, and the artificial leather satisfies the following formulas (1) to (3): L * 1≤55··· (1) 90≥L * 0>50··· (2) ΔL * <-50.78··· (3) Here, L * 1 is the CIE1976L of the design surface * a * b * The lightness index in the color space (L * value), L * 0 is the CIE1976L of the surface opposite to the design surface * a * b * The lightness index in the color space (L * value), ΔL * L is the design surface * The value and L of the surface opposite to the design surface * The difference between the values (CIELAB1976ab brightness difference, L * 1-L * 0); among them, The lightness index is a value measured under the condition of CIE standard light source D65 and a viewing angle of 10°.
2. The light-transmitting device according to claim 1, wherein: The artificial leather is obtained by dyeing the fiber complex with a dye.
Citation Information
Patent Citations
Decorating sheet for illuminating component having leather touch feeling and method for manufacturing illuminating component having leather touch feeling
JP2003071956A
Light permeable sheet and light emitting device
JP2014185404A
Leather-like sheet and leather-like display member
CN111279118A
Inkjet printed artificial leather, and decorative molded body
JP2018127736A